EDUKASI PENGELOLAAN LIMBAH TAHU UNTUK MENINGKATKAN NILAI GIZI PAKAN TENAK DESA KLEPEK KECAMATAN KUNJANG KABUPATEN KEDIRI - Muhamad Ali Tamrin; Moch Uzeir Mustaqfirin (JOURNAL INNOVATION AND COMMUNITY SERVICE, 2024)
Managing home tofu production waste is a significant challenge, especially in the Klepek Village area, Kunjang District, Kediri Regency. Liquid and solid waste resulting from the tofu production process can pollute the environment if it is not processed properly. This program aims to implement an environmentally friendly approach in managing tofu waste, with a focus on utilizing liquid waste into biogas and solid waste into fish feed pellets. This approach is expected to not only reduce negative impacts on the environment but also increase factory efficiency and income through value-added products. Through training activities, workshops and technical assistance, this program will provide new knowledge and skills to tofu factory managers and employees in managing waste efficiently and sustainably. The expected results of this program include reducing waste disposal, increasing the use of alternative energy, and increasing income from waste derivative products.